Hubungan Kecerdasan Interpersonal Dan Intrapersonal Terhadap Hasil Belajar Pendidikan Jasmani Siswa Kelas Atas Sekolah Dasar - Milanton, Sherly; Nur Alif, Muhammad; Ali Rahman, Aam (Gelanggang Olahraga: Jurnal Pendidikan Jasmani dan Olahraga (JPJO), 2025)
This study aims to analyze the relationship between interpersonal and intrapersonal intelligence on the physical education learning outcomes of upper-grade elementary school students. The research employs a quantitative correlational method with a sample of 93 students randomly selected from several elementary schools in Cimanggung District. Data were collected through questionnaires measuring interpersonal and intrapersonal intelligence, along with students’ learning outcomes in physical education. The findings indicate a significant relationship between interpersonal intelligence and learning outcomes (r = 0.773, p < 0.001) as well as between intrapersonal intelligence and learning outcomes (r = 0.766, p < 0.001). These results suggest that the higher a student's interpersonal and intrapersonal intelligence, the better their physical education learning outcomes. Therefore, integrating the development of both types of intelligence into physical education instruction is essential to enhancing the quality of learning. Keywords: Interpersonal Intelligence, Intrapersonal Intelligence, Learning Outcomes, Physical Education